2019
DOI: 10.1136/acupmed-2017-011629
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture and clomiphene citrate for anovulatory infertility: a systematic review and meta-analysis

Abstract: Objective: To evaluate the comparative effectiveness of acupuncture or acupuncture combined with clomiphene citrate (CC) versus CC alone on the outcomes of anovulatory infertility. Methods: A literature search in eight databases yielded nine randomised controlled trials (RCTs) that evaluated the comparative effectiveness of acupuncture and CC in anovulatory infertility. Subsequently, data were extracted and the studies were assessed for the quality of their methodological designs and risk of bias. Meta-analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Compared with CC, acupuncture had better treatment results in pregnancy rate and maximum follicle diameter. At the same time, this meta-analysis also pointed out that CV3, CV4, CV6, ST36, SP6, and EX-CA1 are the most commonly selected for treating anovulatory infertility women, and it suggests that the above acupoints should give priority in future treatment [29].…”
Section: Clinical Effect Of Acupuncture On Infertilitymentioning
confidence: 71%
“…Compared with CC, acupuncture had better treatment results in pregnancy rate and maximum follicle diameter. At the same time, this meta-analysis also pointed out that CV3, CV4, CV6, ST36, SP6, and EX-CA1 are the most commonly selected for treating anovulatory infertility women, and it suggests that the above acupoints should give priority in future treatment [29].…”
Section: Clinical Effect Of Acupuncture On Infertilitymentioning
confidence: 71%
“…In addition, LBR should be considered as a primary outcome of the further IVF meta-analysis study. It was undeniable that clinical pregnancy was a major breakthrough in medicine, but for infertile couples, "take-home" babies were the most important long-term and ultimate outcome of interest (25,26). Moreover, the efficacy was significant just for CPR rather than LBR, which may indicate a higher risk of miscarriage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, most of meta-analyses considered clinical pregnancy rate (CPR) as a primary outcome and neglected the live birth rate (LBR). LBR was an accepted primary outcome in IVF trials (25,26) and its related results need to be further updated. The conflicted results might be not due to the ineffectiveness of acupuncture but rather to the methodological flaws confound acupuncture IVF RCTs.…”
Section: Introductionmentioning
confidence: 99%
“…ere was a meta-analysis [9] of 1,441 ovulation-disorders women showing that the use of acupuncture as a monotherapy significantly improved the rate of pregnancy compared with the use of Clomiphene Citrate (CC) alone. Other researchers [10], using meta-analysis to explore the relationship between acupuncture and patients with low ovarian response (POR), found that acupuncture may improve CPR, AMH, AFC, and the number of retrieved oocytes in women with POR undergoing IVF.…”
Section: Introductionmentioning
confidence: 99%